Impact of Built-up-Litter and Commercial Antimicrobials on Salmonella and Campylobacter Contamination of Broiler Carcasses Processed at a Pilot Mobile Poultry-Processing Unit - Li, KaWang; Lemonakis, Lacey; Glover, Brian; Moritz, Joseph; Shen, Cangliang (Frontiers in Veterinary Science, 2017)
The small scale mobile poultry processing unit (MPPU) produced raw poultry products are of particular food safety concern due to exemption of USDA poultry products inspection act. Limited studies reported the microbial quality and safety of MPPU processed poultry carcasses. This study evaluated the Salmonella and Campylobacter prevalence in broiler ceca and on MPPU processed carcasses and efficacy of commercial antimicrobials against Campylobacter jejuni on broilers. In study I, straight-run Hubbard x Cobb broilers (147) were reared for 38 days on clean-shavings (CS, 75) or built-up-litter (BUL, 72) and processed at a MPPU. Aerobic plate counts, coliforms, Escherichia coli and yeast/molds of carcasses was analyzed on petrifilms. Ceca and carcass samples underwent microbial analyses for Salmonella and Campylobacter spp. using the modified USDA method, and confirmed by API-20e test (Salmonella), latex agglutination immunoassay (Campylobacter) and Gram staining (Campylobacter). Quantitative PCR (CadF-gene) identified the prevalence of C. jejuni and C. coli in ceca and on carcasses. In study II, fresh chilled broiler carcasses were spot-inoculated with C. jejuni (4.5 log10CFU/mL) and then undipped, or dipped into peroxyacetic acid (1,000 ppm), lactic acid (5%), lactic and citric acid blend (2.5%), sodium hypochlorite (69 ppm), or a H2O2-PAA mix (SaniDate® 5.0, 0.25%) for 30 s. Surviving C. jejuni were recovered onto Brucella agar. Aerobic plate counts, coliforms, and E. coli populations were similar (P>0.05) on CS and BUL carcasses. Carcasses of broilers raised on BUL contained a greater (P<0.05) yeast/molds population (2.2 log10CFU/mL) than those reared on CS (1.8 log10CFU/mL). Salmonella was not detected in any ceca samples, whereas 2.8% of the carcasses from BUL were present with Salmonella. Prevalence of Campylobacter spp., C. jejuni was lower (P<0.05) and C. coli was similar (P>0.05) in CS-treated ceca than BUL samples. Prevalence of Campylobacter spp., C. jejuni and C. coli were not different (P>0.05) on CS- and BUL-treated carcasses. All antimicrobials reduced C. jejuni by 1.2–2.0 log CFU/mL on carcasses compared with controls. Hence, raising broilers on CS and applying post-chilling antimicrobial treatment can reduce Salmonella and Campylobacter on MPPU-processed broiler carcasses.